Ekokritik dalam Puisi-Puisi Madura Modern Semerbak Mayang Karya D. Zawawi Imron - Umar Faruq; Ari Ambarwati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study explores the ecological dimensions of Semerbak Mayang, a poetry anthology by D. Zawawi Imron, through an ecocritical lens. Situated within the cultural framework of Madura, these poems reveal a deep interconnection between humans and nature, where natural elements are not merely background settings but living subjects that reflect identity, memory, and ethical consciousness. This research aims to examine the forms, meanings, and ecological messages conveyed in the poems using a qualitative approach and ecocritical theory. The findings indicate that Imron's works are rich in local wisdom, reverence for nature, and subtle critiques of environmental degradation brought about by modernization. Symbols such as the sea, the land, and the wind are employed not only as poetic imagery but as mediums of contemplation and cultural expression. The poems function as an aesthetic space that also embodies environmental advocacy rooted in indigenous perspectives. Ultimately, this research emphasizes the role of literature, particularly poetry, as a powerful tool for ecological awareness and cultural education. By integrating poetic art with ecological insight, Imron’s poetry affirms the relevance of